Injection-based hairy root induction and plant regeneration techniques in Brassicaceae - Jedličková, Veronika; Štefková, Marie; Mandáková, Terezie; Sánchez López, Juan Francisco; Sedláček, Marek; Lysak, Martin A; Robert, Hélène S (Plant methods, 2024)
BACKGROUND: Hairy roots constitute a valuable tissue culture system for species that are difficult to propagate through conventional seed-based methods. Moreover, the generation of transgenic plants derived from hairy roots can be facilitated by employing carefully designed hormone-containing media. RESULTS: We initiated hairy root formation in the rare crucifer species Asperuginoides axillaris via an injection-based protocol using the Agrobacterium strain C58C1 harboring a hairy root-inducing (Ri) plasmid and successfully regenerated plants from established hairy root lines. Our study confirms the genetic stability of both hairy roots and their derived regenerants and highlights their utility as a permanent source of mitotic chromosomes for cytogenetic investigations. Additionally, we have developed an effective embryo rescue protocol to circumvent seed dormancy issues in A. axillaris seeds. By using inflorescence primary stems of Arabidopsis thaliana and Cardamine hirsuta as starting material, we also established hairy root lines that were subsequently used for regeneration studies. CONCLUSION: We developed efficient hairy root transformation and regeneration protocols for various crucifers, namely A. axillaris, A. thaliana, and C. hirsuta. Hairy roots and derived regenerants can serve as a continuous source of plant material for molecular and cytogenetic analyses.
Keywords: Cardamine hirsuta; Asperuginoides axillaris; Plant regeneration; Arabidopsis thaliana; Hairy root; Cytogenetics; Brassicaceae; Transformation; Crucifers